Dehumanisasi ujaran kebencian dalam penggunaan kata ‘lu’ pada komentar Instagram Rachel Vennya - Hira Tri Windasari Ilham; Sajarwa Sajarwa (Universitas Mulawarman, 2023)
The purpose of this study is to determine the discursive representation of the word 'lu' in the speech written on Rachel Vennya's Instagram comments that have the potential to express hatred using the synergy of linguistic corpus methodology and to identify illocutionary speech acts using Searle's pragmatic theory. This study is a qualitative study in which researchers serve as research tools. The research data collocates with the word 'lu' processed using the Sketch Engine Tool. The hate speech corpus was compiled from Rachel Vennya's Instagram comments from 2020 to 2022. The Instagram Comments Scraper tool was used to capture these comments. The total number of utterances is 4,865, with 22,986 words. The word 'lu' appears in 88 different speech patterns in Instagram comments. The collocation analysis also reveals differences in the proclivity to utilize terms in R1 and L1. Apart from 'dakjal' vs 'setan' and 'kya' vs 'kek,' there was also a proclivity to use other words with similar meanings. One example is the colloquial R1 for the word 'anjing' in the (n+lu) pattern. Then, at 48%, directive speech acts dominated the rise of hate speech, followed by expressive speech acts at 33% and assertive speech acts at 19%.